Investigation of Rbx(MA)1−xPbI3(x = 0, 0.1, 0.3, 0.5, 0.75, 1) perovskites as a potential source of P- and N-type materials for PN-junction solar cell - Saleem, Abida; Imran, Muhammad; Arshad, Muhammad; Kamboh, Afzal H.; Khan, Nawazish A.; Haider, Muhammad I. (Applied physics. A, Materials science & processing, 2019)
We report the investigation of monovalent cation rubidium (Rb + )-doped methylammonium lead iodide (CH 3 NH 3 PbI 3 ; MAPbI 3 ; CH 3 NH 3 =MA)-based perovskites. The perovskite MAPbI 3 have large absorber coefficient than silicon and gallium arsenide, long carrier life, and optimal bandgap, low exciton binding energy, and low manufacturing cost make this material ideal for photovoltaic applications. However, material stability is prime concern and major limitation towards the commercialization of perovskite solar cell. The organic part, i.e., MA, is volatile and subject to degradation in humid/oxygen environment. Here, an effort is made to replace the organic part in MAPbI 3 with oxidation stable Rb cation. The Rb x (MA) 1− x PbI 3 ( x = 0–1) materials were synthesized by solution process method followed by thin-film deposition. The post-deposition annealing of all Rb x (MA) 1− x PbI 3 ( x = 0–1) films is carried out at optimized temperature of 100 °C in argon-filled glove box. The pristine MAPbI 3 films have shown tetragonal structure, whereas orthorhombic distortion is observed in all Rb-doped samples. The electron micrographs of doped films have shown dendritic structures which converted into a beautiful thread/wire like structures in all inorganic RbPbI 3 films. Optical studies also show phase transition in Rb-doped samples in two different regions. The absorption intensity observed by photoluminescence studies is increased by six orders of magnitude in partially doped samples. It is observed that the carrier concentration and mobility of the material can be controlled and the conductivity type of the material could be tuned from n-type to p-type by doping with Rb doping. The X-ray photoemission spectroscopy (XPS) showed the oxidation states of Pb and I are + 2 and − 1 in all samples. The intercalation of inadvertent carbon and oxygen in Rb x (MA) 1− x PbI 3 films was also investigated by XPS. It is observed that respective oxygen and carbon-related peaks responsible for decomposition of MAPbI 3 material decrease in intensity in all partially doped samples, showing the stability of the material by introducing oxidation stable Rb. This study also opens a way to the future study of perovskite solar cells with perovskite film as a P–N junction. These partially doped perovskites with enhanced stability and improved optoelectronic properties could be an attractive candidate as light harvesters for photovoltaic device application.